Job Satisfaction Among the Military Personnel in Battalion Infantry Malaysian Army - Zaini, Mohamad (2011)
This study aimed to describe the relationship between job satisfactions towards pay and allowances, and working condition among the Military Personnel of the Malaysian Battalion Infantry Standard in the army, especially among members of other ranks. A total of 130 respondents were tested to determine whether their level of job satisfaction are related to pay and allowances, and working condition that they face on. Based on the test for the hypothesis, there was a significant relationship between pay and allowances, and working condition on job satisfaction in a Malaysian Battalion Infantry Standard, however it depends on the factor of pay and allowances, and working condition faced by their subordinates and other members particularly other ranks in the battalion.